(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Due to climate change, together with the need to reduce the ecological footprint and the future resource shortages, a climate-resilient and resource-conserving architecture must be reinforced. Dealing with the issue of resources not only affects the materialisation of the building, but also the handling of resources on the building site. The interactions between the environment (sun, wind, precipitation), buildings, sealing, plants and people form a complex system in which small changes in few factors can influence the situation on a large scale. In this context, topics such as microclimate improvement around built infrastructure through greening and rainwater management, will gain in importance. The correct assessment of measures for a sustainable and resilient building is extremely complex and time-consuming and requires extensive, multi-layered know-how and experience. This paper analyses the project “House of Learning“ (MAGK Architekten) and its immediate surroundings and focuses on its climate resilience and neutrality, proposing improvement measures based on the interaction of blue and green infrastructure and the building. The potential favourable conditions are evaluated through microclimate simulations and planning principles implying an integral approach which includes landscape gardeners, building planners and constructors, as well as decision-makers.